2020
DOI: 10.3389/fimmu.2020.02140
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in Sepsis

Abstract: Sepsis is a severe state of infection with high mortality. Pathogen-associated molecular patterns and damage-associated molecular patterns (DAMPs) initiate dysregulated systemic inflammation upon binding to pattern recognition receptors. Exosomes are endosome-derived vesicles, which carry proteins, lipids and nucleic acids, and facilitate intercellular communications. Studies have shown altered contents and function of exosomes during sepsis. In sepsis, exosomes carry increased levels of cytokines and DAMPs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 85 publications
(157 reference statements)
0
73
0
Order By: Relevance
“…Exosomes, biological lipid bilayer nanoparticles secreted via the endosomal pathway of cells, have recently emerged as important cargos that carry multiple mediators critical for the pathogenesis of sepsis-associated organ dysfunctions [ 37 ]. Meanwhile, the application of exosomes in sepsis may be a novel approach for sepsis treatment [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes, biological lipid bilayer nanoparticles secreted via the endosomal pathway of cells, have recently emerged as important cargos that carry multiple mediators critical for the pathogenesis of sepsis-associated organ dysfunctions [ 37 ]. Meanwhile, the application of exosomes in sepsis may be a novel approach for sepsis treatment [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes, biological lipid bilayer nanoparticles secreted via the endosomal pathway of cells, have recently emerged as important cargos that carry multiple mediators critical for the pathogenesis of sepsis-associated organ dysfunctions [ 37 ]. Meanwhile, the application of exosomes in sepsis may be a novel approach for sepsis treatment [ 37 39 ]. Recently, circular RNAs have been identified for their enrichment and stability in exosomes, and exosomal circRNAs have potential applications as biomarkers and novel therapeutic targets in human diseases [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The constitution of gut microbiome is altered by sepsis, which may contribute to organ dysfunction [ 51 , 52 ]. S-EVs are thought to be capable of eliciting inflammation by delivering cytokines or damage-associated molecular pattern to target tissues [ 53 ]. In accordance with these notions one can consider that the EVs secreted during sepsis may reshape contents of gut microbiota by direct or indirect transfer of their biologically active contents including pro-inflammatory mediators or miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In systemic lupus erythematosus it was observed that EVs expressed pro-inflammatory immune complexes [ 58 ]. In term of sepsis, there are also several data regarding the contribution of the EVs [ 59 ]. Platelet-derived EVs of septic patients were shown to induce apoptosis in endothelial cells and cardiomyocytes that lead to vascular dysfunctions and cardiomyopathy [ 60 ].…”
Section: Introductionmentioning
confidence: 99%